Cultivation Of Bsf (Black Soldier Fly) As Fish Feed In Sukamaju District, Binjai Barat Sub-District, Binjai City - Sadeli, Achmad; Hilman, Adrian; Hakim, Lukman; Nasution, Delima Lailan Sari; Azhari (Talenta Publisher, 2021)
This activity was conducted in July and November 2020. Partners of this activity are a freshwater fish farmer community located on Jalan Gatot Subroto no. LK 336 IV, Sukamaju, Â Binjai Barat Distirct, Binjai, Sumatera Utara. The main problems faced by partners are 1) Farmers have difficulty in providing fish feed in the form of worms 2) The price of worms continues to increase, so it is difficult for breeders to provide good nutrition 3) Community do not yet know what it flies BSF (Black Soldier Fly) 4) The community does not yet know how to cultivate BSF 5) The community does not know that BSF Maggot is a high protein feed. The purpose of implementing this activity is 1) so that farmers get a replacement feed worm 2) Farmers can get fish feed with good nutrient and reasonably priced 3) BSF Maggot cultivation training, so farmers know 4) as a source of increasing income for freshwater fish farmers. The output target to be achieved from this activity program is that farmers can cultivate and use BSF as freshwater fish feed. Output details of the program produced include 1) training and assistance services for BSF Maggot cultivation 2) Video Activities 3) Scientific articles about mentoring cultivating devotion Maggot BSF. BSF extension and cultivation training activities have been carried out well, and have resulted in video activities on YouTube and also publications in online mass media. The conclusion of this activity partners know the advantages of BSF and can cultivate BSF properly.